Business study seminar (Europe) key issues facing the EU. - Chang, Siau Miin. (2011)
The European Union (EU) is an economic co-operation which operates as a loose federation (Currie, 1997). Comprising 15 western European nation states, the EU has the world's largest domestic market with a population of 370 million, surpassing even that of the U. S. To reap the benefits of this large market, the EU must create a common and stable market for a stronger Europe (The European Commission, 1998a). The path to achieving this larger market, however, is strewn with political, economic as well as social challenges that require the EU's attention and response.